Composite porous lithium ion sieve adsorbent as well as preparation method and application thereof

By using fluoropolymer and binder to jointly build a composite porous adsorbent during the lithium ion sieve adsorbent molding process, the problem of loss of lithium adsorption capacity caused by the use of binders is solved, and efficient and stable lithium adsorption effect is achieved, which is suitable for industrial-scale lithium extraction applications.

CN119838575AActive Publication Date: 2025-04-18ZHENGZHOU UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510085701.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing lithium ion sieve adsorbents during molding process result in loss of lithium adsorption capacity and reduced adsorption rate due to the use of organic binders, limiting their efficiency and economicality in industrial-scale lithium extraction.

Method used

Fluoropolymers are used as additives to collaborate with binder and powder adsorbent precursor to construct a composite porous lithium ion sieve adsorbent, and the rapid capture of lithium ions is achieved through fluorine-lithium bonds, reducing the loss of adsorption capacity during the molding process.

Benefits of technology

It improves the overall adsorption capacity and cycle stability of the composite porous lithium ion sieve adsorbent, enhances its lithium selective adsorption capability in complex aqueous environments, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838575A_ABST
    Figure CN119838575A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of salt lake lithium extraction, and discloses a composite porous lithium ion sieve adsorbent and a preparation method and application thereof, and the preparation method comprises the following steps: uniformly mixing a lithium ion sieve adsorbent precursor, a fluorine-containing polymer, a binder, a pore-forming agent and a solvent to obtain slurry; s2, adding the slurry obtained in the step S1 into a cross-linking agent, and standing and cross-linking to obtain a composite porous lithium ion sieve adsorbent precursor; and performing lithium elution on the composite porous lithium ion sieve adsorbent precursor obtained in the step S2 by using an eluent to obtain the composite porous lithium ion sieve adsorbent. The prepared adsorbent is convenient to recover, has certain mechanical strength, can show relatively good cycle stability, is beneficial to long-term cycle use, and is a lithium adsorption material which is easy to realize industrial application; fluorine atoms in the fluorine-containing polymer serve as atoms with high electronegativity, have high affinity for lithium ions in a water phase, and can assist in achieving efficient and rapid lithium adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium extraction from salt lakes, and in particular to a composite porous lithium ion sieve adsorbent and a preparation method and application thereof. Background Art

[0002] Lithium and its compounds are widely used in energy storage, nuclear industry, medical treatment, aerospace, ceramics, glass and other fields due to their unique physical and chemical properties. Especially in the field of energy storage, lithium occupies an important position and is called the "white oil" in the field of modern energy. At present, we are in a critical period of world food crisis, environmental pollution control and transformation and upgrading of the "dual carbon" industrial structure. Against this background, the development of emerging industries has become an inevitable choice to cope with the shortage of energy resources and the ecological environment crisis. With the rapid development of new energy batteries, as a key raw material in the downstream industrial chain, the demand for lithium has shown a sharp growth trend.

[0003] As one of the important sources of lithium resources in the world, salt lake brine is valued for its rich lithium reserves and relatively low production costs. However, factors such as low lithium concentration, high magnesium-lithium ratio and complex associated environment pose challenges to the effective development of lithium resources in salt lake brine. These factors jointly affect the selectivity and efficiency of the lithium extraction process, making the technology of efficient extraction of liquid lithium resources a research focus in the field of lithium resource development in the future. At present, the technologies for extracting lithium from salt lake brine mainly include precipitation, solvent extraction, electrochemical method and adsorption method. Among them, the adsorption method is considered to be a potential lithium extraction technology due to its simple operation, high selectivity and environmental friendliness. The adsorption method separates lithium from other ions by utilizing the selective adsorption of lithium ions by the adsorbent. However, the selection and design of the adsorbent is the key to the successful application of this technology, and the adsorption capacity, selectivity, stability and regeneration ability of the adsorbent need to be comprehensively considered.

[0004] At present, adsorbents are mainly divided into two categories: organic adsorbents and inorganic adsorbents. Among them, lithium ion sieve adsorbents (LIS) have attracted much attention due to their ability to specifically identify lithium ions. This type of adsorbent has the advantages of controllable production and manufacturing costs and simple synthesis process. It has certain potential for large-scale mass production and large-scale application in industry, and has become a current research hotspot. At present, lithium ion sieve adsorbent materials mainly include titanium adsorbents (LTO) and manganese adsorbents (LMO). LTO and LMO usually exist in the form of powders. In actual application, they face problems such as difficult powder recovery and serious losses. These problems limit their efficiency and economy in industrial-scale lithium extraction. Therefore, adsorbent molding has become one of the most important research directions at present. Existing molding technologies include granulation, magnetization, foaming, film forming, etc.

[0005] The Chinese invention patent "A method for granulating and forming a lithium ion sieve for liquid lithium recovery" with announcement number CN116786076A uses a double binder and a pore-forming agent to mix with lithium ion sieve precursor powder to prepare a slurry for granulation, and obtains a formed lithium ion sieve by elution. The spherical lithium ion sieve prepared by this invention has a certain mechanical strength, which overcomes the problem that the current powder lithium ion sieve is difficult to directly apply and recycle, but its adsorption capacity loss exceeds 40% compared with the powder adsorbent. At present, the lithium ion sieve forming technology mostly uses organic high molecular polymers as binders or additives, etc., and its use has the disadvantage of blocking some adsorption sites, which will cause the loss of adsorption capacity and the reduction of adsorption rate, and weaken the overall adsorption performance of the adsorbent.

[0006] In order to achieve a sustainable supply of lithium, a composite porous lithium ion sieve adsorbent and its preparation method and application are urgently needed to solve the above technical problems. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a composite porous lithium ion sieve adsorbent and a preparation method and application thereof, which can minimize the negative impact of the use of a binder on the lithium adsorption performance while molding the powder adsorbent into a granular adsorbent form that is more suitable for industrial applications, thereby obtaining a lithium adsorbent material with excellent performance.

[0008] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0009] A method for preparing a composite porous lithium ion sieve adsorbent comprises the following steps:

[0010] S1, mixing a lithium ion sieve adsorbent precursor, a fluorine-containing polymer, a binder, a pore-forming agent, and a solvent to obtain a slurry;

[0011] S2, adding the slurry obtained in step S1 to a cross-linking agent, and obtaining a composite porous lithium ion sieve adsorbent precursor after standing and cross-linking;

[0012] S3, using an eluent to elute lithium from the composite porous lithium ion sieve adsorbent precursor obtained in step S2 to obtain a composite porous lithium ion sieve adsorbent.

[0013] Preferably, in the step S1, in the obtained slurry, a lithium ion sieve adsorbent precursor, a fluorine-containing polymer, a binder, and a pore-forming agent constitute a mixed material, and the mixed material includes the following components in mass fractions: 20-40wt% of lithium ion sieve adsorbent precursor, 10-40wt% of fluorine-containing polymer, 10-40wt% of binder, and 5-20wt% of pore-forming agent; the mass ratio of the mixed material to the solvent is 1:(2-10).

[0014] Preferably, in step S1, the lithium ion sieve adsorbent precursor is at least one of a titanium-based adsorbent precursor and a manganese-based adsorbent precursor.

[0015] Preferably, the titanium adsorbent precursor is Li2TiO3, Li4Ti5O 12 At least one of the following; the manganese-based adsorbent precursor is LiMn2O4, Li4Mn5O 12 , Li 1.6 Mn 1.6 At least one of O5.

[0016] Preferably, in step S1, the viscosity-average molecular weight of the fluorine-containing polymer is 1000-50000; the fluorine-containing polymer is at least one of polyvinylidene fluoride (PVDF), polyperfluoroethylene propylene (FEP), perfluoroalkoxy polymer (PFA), and polytetrafluoroethylene (PTFE).

[0017] More preferably, the viscosity average molecular weight of the fluorine-containing polymer is 2,000 to 10,000.

[0018] Preferably, in step S1, the average molecular weight of the binder is 1000-200000; the binder is at least one of sodium alginate (SA), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), and polyacrylonitrile (PAN).

[0019] Preferably, in step S1, the pore-forming agent is at least one of nano-calcium carbonate, nano-magnesium carbonate, nano-manganese carbonate and nano-zinc carbonate.

[0020] Preferably, in step S1, the solvent is at least one of water, N,N-dimethylformamide (DMF), ethanol, N-methylpyrrolidone (NMP), and dimethylacetamide (DMAC).

[0021] Preferably, in step S2, the crosslinking agent is at least one of water, calcium chloride solution, and boric acid solution; the volume ratio of the crosslinking agent to the slurry is (5-10):1; and the concentration of the calcium chloride solution and the boric acid solution does not exceed 1 mol / L.

[0022] Preferably, in step S2, the slurry is added to the cross-linking agent and then allowed to stand for cross-linking for 8 to 12 hours, followed by filtration, washing and drying to obtain a composite porous lithium ion sieve adsorbent precursor; the drying temperature is 50 to 80° C., and the drying time is 4 to 12 hours.

[0023] Preferably, in step S2, the slurry is added to the cross-linking agent in a dropwise manner, with a dropwise addition rate of 30 to 40 drops / min.

[0024] Preferably, in step S3, the eluent is at least one of a hydrochloric acid solution, a nitric acid solution, and a sulfuric acid solution; and the concentration of the eluent is 0.1 to 0.5 mol / L.

[0025] Preferably, in step S3, the composite porous lithium ion sieve adsorbent is eluted with an eluent to remove lithium ions; then filtered, washed and dried to obtain the composite porous lithium ion sieve adsorbent; the solid-liquid ratio of the composite porous lithium ion sieve adsorbent precursor to the eluent is (1-50):1, and the unit of the solid-liquid ratio is g:L; the elution temperature is 20-60°C, the elution time is 2-24h, and the stirring speed during the elution process is 100-600r / min; the drying temperature is 50-80°C, and the drying time is 4-12h.

[0026] The present invention also includes a composite porous lithium ion sieve adsorbent, which is prepared by the above preparation method.

[0027] The composite porous lithium ion sieve adsorbent prepared by the invention is in granular form.

[0028] The present invention also includes the use of the composite porous lithium ion sieve adsorbent in extracting lithium from salt lakes.

[0029] Working principle:

[0030] The method of the present invention uses a fluorine-containing polymer as an additive, and cooperates with a binder and a powder adsorbent precursor (herein referred to as the "lithium ion sieve adsorbent precursor" used in the present invention) to construct a molded composite porous lithium ion sieve adsorbent with certain mechanical properties and excellent adsorption properties. The fluorine atoms in the fluorine-containing polymer have a high affinity for lithium, and can construct a fluorine-lithium bond with a certain binding force with the lithium ions in the aqueous phase, thereby achieving rapid capture of lithium ions, effectively improving the overall adsorption capacity of the composite porous lithium ion sieve adsorbent, and simultaneously reducing the loss of lithium adsorption capacity caused by the use of organic binders during the molding process. The composite porous lithium ion sieve adsorbent has a certain mechanical strength due to molding, exhibits excellent cycle stability, and is conducive to long-term cyclic use. At the same time, the composite porous lithium ion sieve adsorbent exhibits a certain selectivity, and can achieve highly selective adsorption of lithium in a complex aqueous environment.

[0031] Beneficial effects:

[0032] (1) The composite porous lithium ion sieve adsorbent prepared by the present invention is easy to recycle, has a certain mechanical strength, can show good cycle stability, is conducive to long-term recycling, and is a lithium adsorption material that is easy to realize industrial application;

[0033] (2) The fluorine atom in the fluorinated polymer, as an atom with strong electronegativity, has a high affinity for lithium ions in the aqueous phase, which can assist in achieving efficient and rapid lithium adsorption;

[0034] (3) The fluorinated polymer can selectively adsorb lithium ions together with the lithium ion sieve adsorbent, so that the composite porous lithium ion sieve adsorbent exhibits higher adsorption selectivity;

[0035] (4) The preparation method is simple and environmentally friendly, without the need for high temperature and high pressure, thus reducing energy consumption and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The selectivity of the adsorbent samples prepared in Example 1 and Comparative Example 1 of the present invention to different metal ions in brine solution E;

[0037] Figure 2 The lithium ion adsorption capacity diagram of the adsorbent samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention in brine solution A at different time periods. DETAILED DESCRIPTION

[0038] The present invention is further described in detail with reference to specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses industrial purity or conventional purity used in the art.

[0040] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.

[0041] Example 1

[0042] A method for preparing a composite porous lithium ion sieve adsorbent comprises the following steps:

[0043] Weigh 1g of SA with a molecular weight of 20000, add 49mL of deionized water to prepare 50mL of SA solution with a concentration of 2wt%. After complete dissolution, add 2g of titanium adsorbent precursor Li2TiO3, 2g of PVDF with a molecular weight of 5000 and 1g of nano calcium carbonate, and stir at room temperature at a stirring speed of 300r / min for 4h to obtain a slurry. Slowly add the slurry to 500mL of 0.1mol / L calcium chloride solution at a dropping speed of 30-40 drops / min to form gel balls. After standing and crosslinking for 12h, wash it three times with pure water and place the product in a 50℃ oven to dry for 12h to prepare a shaped composite porous lithium ion sieve adsorbent precursor. Weigh an appropriate amount of composite precursor according to a solid-liquid ratio of 10g:1L and place it in a 0.2mol / L dilute HCl solution for elution treatment to remove lithium ions. The elution temperature is 30℃, the elution time is 8h, and the stirring speed is 200r / min. After the acid elution treatment is completed, the product is washed with pure water until the washing liquid is neutral, and then placed in a 60° C. oven and dried for 8 hours to obtain a composite porous titanium-based lithium ion sieve adsorbent.

[0044] Example 2

[0045] A method for preparing a composite porous lithium ion sieve adsorbent comprises the following steps:

[0046] Weigh 4 g of PVA with a molecular weight of 74800 and mix with 36 mL of deionized water to prepare 40 mL of 10 wt% PVA solution. After the solution is completely dissolved, 4 g of Li4Mn5O 12 2g of PVDF with a molecular weight of 5000 and 1g of nano magnesium carbonate were added thereto, and a uniformly mixed slurry was obtained after stirring at 500r / min for 6h at 25°C. The slurry was added drop by drop at a drop rate of 30-40 drops / min into 250mL of a 0.8mol / L boric acid solution to form gel balls. After standing in the solution for 8h for crosslinking, the product was washed three times with pure water and placed in an oven at 80°C for 4h to obtain a composite porous lithium ion sieve adsorbent precursor. According to the solid-liquid ratio of 20g:1L, an appropriate amount of composite precursor was weighed and placed in a 0.3mol / L dilute HCl solution for elution treatment to remove lithium ions. The elution temperature was 40°C, the elution time was 4h, and the stirring speed was 200r / min. After the acid elution treatment was completed, the product was washed with pure water until the washing liquid was neutral. It was placed in an oven at 80°C for 4h to obtain a composite porous manganese lithium ion sieve adsorbent.

[0047] Embodiment 3:

[0048] A method for preparing a composite porous lithium ion sieve adsorbent comprises the following steps:

[0049] Weigh 2 g of PVC with a molecular weight of 1.5 wt % and dissolve it in 38 mL of DMF to obtain 40 mL of 5 wt % PVC solution. After it is completely dissolved, add 3 g of titanium adsorbent precursor Li4Ti5O 12 , 2g of polyperfluoroethylene propylene with a molecular weight of 7000 and 1g of nano manganese carbonate were stirred at 60°C at a stirring speed of 300r / min for 8h to obtain a uniformly mixed slurry. The slurry was added drop by drop into 500mL of deionized water at a drop rate of 30-40 drops / min to form gel balls. After standing and crosslinking for 12h, it was washed three times with pure water and anhydrous ethanol respectively, and then the product was placed in a 60°C oven and dried for 8h to prepare a composite porous lithium ion sieve adsorbent precursor. According to the solid-liquid ratio of 40g:1L, an appropriate amount of composite precursor was weighed and placed in a 0.5mol / L dilute HNO3 solution for elution treatment to remove lithium ions. The elution temperature was 30°C, the elution time was 2h, and the stirring speed was 100r / min. After the acid elution treatment was completed, the product was washed with pure water until the washing liquid was neutral. It was placed in a 60°C oven and dried for 8h to obtain a composite porous titanium lithium ion sieve adsorbent.

[0050] Example 4

[0051] A method for preparing a composite porous lithium ion sieve adsorbent comprises the following steps:

[0052] Weigh 3g of PAN with a molecular weight and dissolve it in 27mL of DMAC to obtain 30mL of 10wt% PAN solution. After it is completely dissolved, add 2g of manganese adsorbent precursor LiMn2O4, 2g of perfluoroalkoxy polymer with a molecular weight of 4000 and 1g of nano zinc carbonate, and stir at 80°C at a stirring speed of 300r / min for 6h to obtain a uniformly mixed slurry. The slurry is added drop by drop into 250mL of deionized water at a dropping speed of 30-40 drops / min to form gel balls. After standing and crosslinking for 12h, it is washed three times with pure water and anhydrous ethanol respectively, and then the product is placed in an 80°C oven and dried for 6h to prepare a formed composite porous lithium ion sieve adsorbent precursor. According to the solid-liquid ratio of 5g:1L, an appropriate amount of composite precursor is weighed and placed in a 0.1mol / L dilute H2SO4 solution for elution treatment to remove lithium ions. The elution temperature is 20°C, the elution time is 24h, and the stirring speed is 400r / min. After the acid elution treatment is completed, the product is washed with pure water until the washing liquid is neutral. It is placed in a 50°C oven and dried for 12h to obtain a composite porous manganese lithium ion sieve adsorbent.

[0053] Example 5

[0054] A method for preparing a composite porous lithium ion sieve adsorbent comprises the following steps:

[0055] Weigh 1g of SA with a molecular weight of 20,000, add 49mL of deionized water to prepare 50mL of 2wt% SA solution, and add 2g of manganese adsorbent precursor Li after it is completely dissolved. 1.6 Mn 1.6 O5, 2g PTFE with a molecular weight of 8000 and 1g nano calcium carbonate were stirred at room temperature at a stirring speed of 300r / min for 4h to obtain a slurry. The slurry was added drop by drop at a drop rate of 30-40 drops / min into 550mL calcium chloride solution with a concentration of 0.1mol / L to form gel balls. After standing for crosslinking for 12h, the product was washed three times with pure water and placed in a 60℃ oven to dry for 10h to prepare a shaped composite porous lithium ion sieve adsorbent precursor. According to the solid-liquid ratio of 2g:1L, an appropriate amount of composite precursor was weighed and placed in a 0.1mol / L dilute HCl solution for elution treatment to remove lithium ions. The elution temperature was 60℃, the elution time was 6h, and the stirring speed was 600r / min. After the acid elution treatment, the product was washed with pure water until the washing liquid was neutral. It was placed in a 60℃ oven and dried for 6h to obtain a composite porous manganese lithium ion sieve adsorbent.

[0056] Comparative Example 1

[0057] The only difference between this comparative example and Example 1 is that the shaped titanium-based adsorbent is prepared without adding the fluorine-containing polymer PVDF, and the other conditions and parameters are exactly the same as those in Example 1.

[0058] Comparative Example 2

[0059] The only difference between this comparative example and Example 1 is that no pore-forming agent is added to prepare the shaped titanium-based adsorbent, and the other conditions and parameters are exactly the same as those in Example 1.

[0060] Comparative Example 3

[0061] In this comparative example, an appropriate amount of powdered titanium precursor Li2TiO3 was weighed according to a solid-liquid ratio of 10g / L and placed in a 0.2mol / L dilute HCl solution for elution treatment to remove lithium ions. The elution temperature was 30°C, the elution time was 8h, and the stirring speed was 200r / min. After the acid elution treatment was completed, the product was washed with pure water until the washing liquid was neutral. It was placed in a 60°C oven and dried for 8h to obtain a powdered titanium lithium ion sieve adsorbent.

[0062] Comparative Example 4

[0063] In this comparative example, an appropriate amount of powdered manganese precursor Li4Mn5O was weighed according to a solid-liquid ratio of 20 g / L. 12Place it in a 0.3 mol / L dilute HCl solution for elution to remove lithium ions, the elution temperature is 40°C, the elution time is 4h, and the stirring speed is 100r / min. After the acid elution treatment is completed, wash the product with pure water until the washing liquid is neutral. Place it in an 80°C oven and dry it for 4h to obtain a powdered manganese lithium ion sieve adsorbent.

[0064] Testing and Characterization:

[0065] Adsorption experiment: The adsorption performance of the adsorbents prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was studied and compared through adsorption experiments. Several lithium-containing brine solutions with different ion components were prepared, and their components are listed in Table 1.

[0066] Table 1 Solution composition used in adsorption experiments

[0067] Brine solution A B C D E <![CDATA[Li + (g / L)]]> 1.06 0.38 1.74 1.79 0.40 <![CDATA[Na + (g / L)]]> - 55.13 44.58 3.15 1.35 <![CDATA[K + (g / L)]]> - 8.68 0.87 1.86 0.48 <![CDATA[Mg 2+ (g / L)]]> - - - 86.40 120.33 pH 12.5 9.6 12.6 7.2 6.2

[0068] In the above table, "-" indicates that the brine solution does not contain the corresponding ions.

[0069] 1g of the prepared shaped adsorbents of the above embodiments and comparative examples were added to 500mL of lithium-containing solution, and the adsorption and lithium extraction experiment was carried out in a 30°C water bath with an oscillation speed of 200r / min. Samples were taken regularly until the adsorption reached equilibrium with a constant lithium concentration. The lithium ion concentration in the solution before and after adsorption was measured by inductively coupled plasma (ICP-OES) to calculate its lithium adsorption capacity. The adsorption capacity calculation formula of the composite adsorbent is: In the formula, Q p The lithium adsorption capacity of the composite adsorbent converted to the mass of the powdered lithium ion sieve, mg / g; C0 and C e are the lithium ion concentrations in the solution at the initial and equilibrium adsorption times, mg / L; V is the volume of the lithium-containing solution, L; m is the mass of the composite adsorbent, g; and w is the content of the powdered lithium ion sieve in the composite adsorbent, %. Separation factor The calculation formula is: M is other metal ions, K d is the distribution coefficient.

[0070] The adsorption of lithium ions by various prepared adsorbents in different brines was tested, and the relevant adsorption experimental data are summarized in Table 2.

[0071] Table 2 Summary of adsorption data

[0072]

[0073]

[0074] In the above table, those with relevant results indicate that relevant adsorption tests have been conducted; those with no relevant results and filled with “-” indicate that relevant adsorption tests have not been conducted.

[0075] In the process of forming a gel network by cross-linking between the powder adsorbent and the binder, some adsorption sites are covered by the organic binder, which hinders the effective contact between the adsorbent and the lithium ions in the solution. In addition, the cross-linking process may affect the pore structure of the adsorbent, thereby affecting the diffusion and transmission of lithium ions in the adsorbent. Therefore, the powder adsorbent usually has a reduced adsorption capacity after molding. As an important indicator for judging the adsorption performance of the adsorbent, the adsorption capacity may vary greatly under different adsorption conditions. For lithium ion sieves, the adsorption capacity increases with the increase of the initial lithium concentration and the pH of the solution. In the adsorption experiment of pure lithium solution A with a pH of 12.5, the adsorption capacity of the sample in Example 1 is 50.42 mg / g, and the sample in Comparative Example 1 is 44.65 mg / g. In Example 1, the added fluorine-containing polymer can adsorb lithium ions in the solution based on the principle of lithium bond bonding due to the affinity of fluorine atoms for lithium. This can not only assist in achieving efficient and rapid lithium adsorption, but also compensate to a certain extent for the loss of adsorption capacity of the powder LTO caused by the molding process. The sample prepared in Example 1 was subjected to a cyclic adsorption experiment, and after ten cycles, its adsorption capacity was still maintained at 98.33% of the initial adsorption. The results show that the composite porous lithium ion sieve adsorbent prepared by the present invention has a certain cyclic stability, which is conducive to long-term cyclic use in industrial applications.

[0076] The adsorption selectivity of the samples of Example 1 and Comparative Example 1 in brine solution E was compared and investigated. Figure 1 As shown, the selectivity of the adsorbent samples prepared in Example 1 of the present invention and Comparative Example 1 for different metal ions in brine solution E. It can be seen that the composite porous lithium ion sieve adsorbent prepared by adding fluorine-containing polymer obtained in Example 1 shows excellent selectivity for lithium ions. The composite porous lithium ion sieve adsorbent still has excellent lithium selective extraction and separation capabilities in high magnesium-lithium ratio solutions, and has good application prospects.

[0077] Figure 2The lithium ion adsorption capacity diagram of the adsorbent samples prepared by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention in brine solution A at different times. It can be seen from the figure that the adsorption capacity of all samples gradually increases with the increase of time, and rapid adsorption is carried out within 6 hours after the adsorption begins. At 6 hours, the adsorption capacity reaches 86.1%, 79.1% and 81.7% of the equilibrium adsorption capacity, respectively. In the early stage of adsorption, there are many adsorption sites on the surface of the sample, which can quickly adsorb free lithium ions in the aqueous phase. The adsorption kinetics of the samples were analyzed using the quasi-second-order kinetic equation, and the relevant parameters are listed in Table 3. Rate constant k2: Example 1>Comparative Example 2>Comparative Example 1, the sample of Example 1 shows the fastest adsorption rate. The fluorine-containing polymer incorporated into the sample of Example 1 has a certain affinity for lithium, and the pore former added at the same time can promote the formation of a rich pore structure inside the adsorbent, so it shows a relatively fast adsorption rate.

[0078] Table 3 Quasi-second-order adsorption kinetics fitting parameters

[0079] <![CDATA[Q R,实际 (mg / g)]]> <![CDATA[K2(g / mg·h)]]> <![CDATA[Q R,理论 (mg / g)]]> <![CDATA[R 2 ]]> Example 1 50.42 0.0153 55.31 0.9975 Comparative Example 1 42.65 0.0099 48.19 0.9940 Comparative Example 2 47.02 0.0121 52.47 0.9957

[0080] The present invention uses a binder to prepare a shaped composite adsorbent from a powdered adsorbent, thereby avoiding material loss in subsequent recycling and effectively ensuring the recyclability of the adsorbent. At the same time, it provides a certain mechanical strength, improves the stability and service life of the molding material, and is conducive to long-term industrial recycling.

[0081] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite porous lithium ion sieve adsorbent, characterized in that: The following steps are involved: S1, mixing a lithium ion sieve adsorbent precursor, a fluorine-containing polymer, a binder, a pore-forming agent, and a solvent to obtain a slurry; S2, adding the slurry obtained in step S1 to a cross-linking agent, and obtaining a composite porous lithium ion sieve adsorbent precursor after standing and cross-linking; S3, using an eluent to elute lithium from the composite porous lithium ion sieve adsorbent precursor obtained in step S2 to obtain a composite porous lithium ion sieve adsorbent.

2. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In the step S1, in the obtained slurry, a lithium ion sieve adsorbent precursor, a fluorine-containing polymer, a binder, and a pore-forming agent constitute a mixed material, and the mixed material includes the following components in mass fractions: 20-40wt% of lithium ion sieve adsorbent precursor, 10-40wt% of fluorine-containing polymer, 10-40wt% of binder, and 5-20wt% of pore-forming agent; the mass ratio of the mixed material to the solvent is 1:(2-10).

3. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In the step S1, the lithium ion sieve adsorbent precursor is at least one of a titanium-based adsorbent precursor and a manganese-based adsorbent precursor; In the step S1, the viscosity average molecular weight of the fluorine-containing polymer is 1000-50000; the fluorine-containing polymer is at least one of polyvinylidene fluoride, polyperfluoroethylene propylene, perfluoroalkoxy polymer and polytetrafluoroethylene.

4. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In the step S1, the average molecular weight of the binder is 1000-200000; the binder is at least one of sodium alginate, polyvinyl alcohol, polyvinyl chloride, and polyacrylonitrile; In step S1, the pore-forming agent is at least one of nano-calcium carbonate, nano-magnesium carbonate, nano-manganese carbonate, and nano-zinc carbonate; In the step S1, the solvent is at least one of water, N,N-dimethylformamide, ethanol, N-methylpyrrolidone, and dimethylacetamide.

5. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In step S2, the crosslinking agent is at least one of water, calcium chloride solution, and boric acid solution; the volume ratio of the crosslinking agent to the slurry is (5-10):1; and the concentration of the calcium chloride solution and the boric acid solution does not exceed 1 mol / L.

6. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In the step S2, the slurry is added to the cross-linking agent and then allowed to stand for cross-linking for 8 to 12 hours, followed by filtration, washing and drying to obtain a composite porous lithium ion sieve adsorbent precursor; the drying temperature is 50 to 80° C., and the drying time is 4 to 12 hours.

7. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In step S3, the eluent is at least one of a hydrochloric acid solution, a nitric acid solution, and a sulfuric acid solution; and the concentration of the eluent is 0.1 to 0.5 mol / L.

8. The method for preparing a composite porous lithium ion sieve adsorbent according to claim 1, characterized in that: In the step S3, the composite porous lithium ion sieve adsorbent is eluted with an eluent to remove lithium ions; then filtered, washed, and dried to obtain the composite porous lithium ion sieve adsorbent; The solid-liquid ratio of the composite porous lithium ion sieve adsorbent precursor to the eluent is (1-50):1, and the unit of the solid-liquid ratio is g:L; the elution temperature is 20-60°C, the elution time is 2-24h, and the stirring speed during the elution process is 100-600r / min; The drying temperature is 50-80°C and the drying time is 4-12 hours.

9. Composite porous lithium ion sieve adsorbent, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the composite porous lithium ion sieve adsorbent as claimed in claim 9 in extracting lithium from salt lakes.

Citation Information

Patent Citations

  • Lithium ion sieve granulation forming method for liquid lithium recovery

    CN116786076A

  • Preparation method and application of lithium-titanium type ion sieve composite membrane

    CN106622170A

  • Preparation method of granular lithium adsorbent

    CN109225124A

  • Preparation method of membrane-shaped lithium ion sieve adsorbent

    CN114130375A

  • Method for preparing lithium ion sieve adsorbent particles and application

    CN116328713A